1996
DOI: 10.1037/0022-006x.64.5.868
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting and retaining low-income Latinos in psychotherapy research.

Abstract: This article offers suggestions for recruiting and retaining low-income Latinos in treatment studies. Because Latinos underuse traditional mental health services, places such as medical centers or churches with large Latino constituents are suggested as useful alternative sources. To keep Latinos in research protocols, providing culturally sensitive treatments are necessary. Culturally sensitive treatments should incorporate families as part of recruitment efforts, particularly older men in the family. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
170
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(174 citation statements)
references
References 41 publications
4
170
0
Order By: Relevance
“…Most previous accounts of recruiting study participants from ethnically diverse populations come from clinical trials. 2,7,8,10,[20][21][22][23][24][25] Investigators have found that using recruiters from the same ethnic background as the study population, or using community leaders as intermediaries, can help. Instilling trust is important.…”
Section: Strategies For Motivating Latino Couples' Participation In Qmentioning
confidence: 99%
“…Most previous accounts of recruiting study participants from ethnically diverse populations come from clinical trials. 2,7,8,10,[20][21][22][23][24][25] Investigators have found that using recruiters from the same ethnic background as the study population, or using community leaders as intermediaries, can help. Instilling trust is important.…”
Section: Strategies For Motivating Latino Couples' Participation In Qmentioning
confidence: 99%
“…This issue is especially common in studies of urban, minority poor populations. 23,24 The turnover in student therapists affected some participants' willingness to be transferred to new therapists. Motivation to continue may have waned for some clients as a result of a mismatch of the intervention components to women' s perceived needs.…”
Section: 22mentioning
confidence: 99%
“…39,40 These factors includes the study not meeting participants' needs, or possibly creating additional stress on their health, time and efforts. Recruitment of an adequate number and variety of subjects and families is critical to the success of any family study.…”
Section: Subjects' Recruitment and Enrollmentmentioning
confidence: 99%